Necropsy Validation of a Novel Method for Left Ventricular Mass Quantification in Porcine Transthoracic and Transdiaphragmal Echocardiography - Kristensen, Charlotte Burup; Sattler, Stefan Michael; Lubberding, Anniek Frederike; Tfelt-Hansen, Jacob; Jespersen, Thomas; Hassager, Christian; Mogelvang, Rasmus (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Increased left ventricular mass (LVM) is one of the most powerful predictors of adverse cardiovascular events. Clinical evaluation requires reliable, accurate and reproducible echocardiographic LVM-quantification to manage patients. For this purpose, we have developed a novel two-dimensional (2D) method based on adding the mean wall thickness to the left ventricular volume acquired by the biplane method of discs, which has recently been validated in humans using CMR as reference value. We assessed the hypothesis that the novel method has better accuracy than conventional 1D methods, when compared to necropsy LVM in pigs Materials and Methods: Echocardiography was performed during anaesthesia in thirty-four Danish Landrace pigs, weight 47-59 kg. All pigs were euthanized, cardiac necropsy was performed and the left ventricle (LV) was trimmed and weighed for necropsy LVM. Trans-thoracic echocardiography (TTE) was applied for parasternal images. Trans-diaphragmatic echocardiography (TDE) was applied for the apical images, which are otherwise difficult to obtain in pigs. We compared one-dimensional (1D) and two-dimensional (2D) methods, including the novel 2D-method based on adding the mean wall thickness to the LV volume acquired by the biplane model of discs. Results: Necropsy LVM was 132±11g (mean±SD). The novel method had better accuracy than other methods (mean difference±95% limits of agreement; coefficients of variation; standard error of the estimate, Pearson’s correlation). Novel (-1±20g; 8%; 11g; r=0.70), Devereux (+26±37g; 15%; 33g; r=0.52), Area-Length (+27±34g; 13 %; 33g; r=0.63), Truncated Ellipsoid (+10±30g; 12%; 19g; r=0.63), biplane endo-/epicardial tracing (-3±2g; 10%; 14g; r=0.57). No proportional bias in linear regression was detected for any method, when compared to necropsy LVM. Conclusion: We confirm high accuracy of the novel 2D-based method compared to conventional 1D/2D-methods.